2015
DOI: 10.1097/prs.0000000000001641
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Transfers to Restore Upper Extremity Function in Cervical Spinal Cord Injury

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 50 publications
0
71
2
1
Order By: Relevance
“…Some surgeons have suggested that motor axons preferentially reinnervate sensory pathways. 4,21 Fox et al 12 have also observed the absence of M4 finger flexion strength recovery following transfer of the nerve to the brachialis to median nerve motor fascicles in the arm. In contrast, Krasuski and Kiwerski 19 observed M4 finger flexion strength recovery in 16 of 42 tetraplegic patients in whom the branch to the brachialis and the lateral antebrachial cutaneous nerve were transferred to the median nerve.…”
Section: Discussion Restoration Of Finger Flexionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some surgeons have suggested that motor axons preferentially reinnervate sensory pathways. 4,21 Fox et al 12 have also observed the absence of M4 finger flexion strength recovery following transfer of the nerve to the brachialis to median nerve motor fascicles in the arm. In contrast, Krasuski and Kiwerski 19 observed M4 finger flexion strength recovery in 16 of 42 tetraplegic patients in whom the branch to the brachialis and the lateral antebrachial cutaneous nerve were transferred to the median nerve.…”
Section: Discussion Restoration Of Finger Flexionmentioning
confidence: 96%
“…More recently the use of distal nerve transfers has emerged as an adjunct therapy to improve upper limb function in patients with tetraplegia. 6,12 In this strategy, by crossing peripheral nerves, axons from motoneurons that originate above the lesion level and have functional cortical drive are rerouted to reinnervate target muscles that are normally innervated by motoneurons located below the spinal cord lesion. In patients with midcervical spinal cord injuries, distal nerve transfer resulted in predictable restoration of elbow and finger extension with a single surgery, no postoperative casting, and only 1 day of hospitalization.…”
mentioning
confidence: 99%
“…Candidacy for nerve transfer surgery has yet to be definitively outlined. Our previous work [9,10,24], as well as contributions from others [6][7][8][11][12][13]25,26], suggest that results after nerve transfer surgery are promising, although studies [27,28] show variable outcomes. This emphasizes the need for careful and comprehensive preoperative patient evaluation using standardized functional assessments to better define surgical candidacy and outcomes of nerve transfer surgery in patients with SCI.…”
Section: Discussionmentioning
confidence: 97%
“…The limitations of tendon transfers include limited tendon/muscle donors and a long duration of postoperative immobilization. Newer treatment options such as nerve transfer surgery [1][2][3][5][6][7][8][9][10][11][12][13] could improve eligibility or desirability for reconstructive surgery.…”
Section: Introductionmentioning
confidence: 99%
“… 32) There are a few significant nerve transfer procedures that showed predictable results. 6 7 11 17 18 20 21) …”
Section: What Kind Of Nerve Transfer Surgery Can Be Done?mentioning
confidence: 99%